Pemanfaatan Konseling Sebaya dalam Meningkatkan Psychological Wellbeing Mahasiswa Iain Curup - Syamsul Rizal; febriansyah; Fadila (Institut Agama Islam Negeri Curup, 2026)
IAIN Curup has an important role in supporting students' holistic development, including psychological well-being. Academic, social, and environmental adaptation pressures often increase student stress and anxiety. The suicide case at IAIN Curup highlights the need for in-depth understanding and support for student mental health. Peer counseling, where students help others with similar backgrounds, is recognized as effective in improving psychological well-being. This research uses a mix method to explore the use of peer counseling at IAIN Curup, including the challenges and obstacles in its implementation. The results showed that peer counseling improved psychological well-being through moral support and collaboration with academic staff and mental health professionals. However, major challenges such as stigma against mental health and low student awareness hinder the effectiveness of the program. Barriers to trust in peer counselors' advice also arise due to doubts about their competence. This research suggests the development of peer counseling strategies that are relevant to the IAIN Curup context and integration with the wider mental health system. It is hoped that these results can become a reference for other universities in facing similar challenges and improving students' psychological well-being holistically.